Evaluation of FSVA Use as an Indicator in Tanjungpinang City Food Security Planning Process - Yesi Perdeawati; Hamid Haikal (Journal Governance Bureaucratic Review, 2026)
This study evaluates the use of the Food Security and Vulnerability Atlas (FSVA) as an indicator-based instrument in the food security planning process of Tanjungpinang City. The issue is important because Tanjungpinang, as an urban and archipelagic area, has limited agricultural land, depends on food supplies from outside the region, and faces uneven socioeconomic and basic service conditions across its wards. The purpose of this study is to assess how FSVA indicators can describe local food security conditions, identify vulnerable areas, and support evidence-based planning for targeted policy interventions. This research employed a quantitative descriptive approach using secondary data from relevant government institutions, including data on food supply facilities, low-welfare population, transportation connectivity, clean water access, and health personnel. The data were analyzed through individual indicator analysis, standardization, weighting, composite scoring, and spatial classification into six priority groups. The findings show that Tanjungpinang City is generally in a relatively food-secure condition, with no ward classified as Priority 1. However, one ward is classified as Priority 2, one ward as Priority 3, one ward as Priority 4, seven wards as Priority 5, and eight wards as Priority 6. Senggarang and Dompak require particular attention because their vulnerability is influenced by low-income households, limited clean water access, and an unequal ratio of health personnel. The study concludes that FSVA is useful not only as a vulnerability mapping tool but also as a planning framework that links data, spatial analysis, causal factors, and policy interventions to strengthen sustainable urban food security.